Islamic Legal Education and Social Transformation: A Study of Community's Critical Acceptance of the "Uang Pelangkah" Tradition - Sabila, Ahda; Alamsyah, Alamsyah; Fikri, Arif (ETDC: Indonesian Journal of Research and Educational Review, 2025)
This article examines the tension between Islamic Law (Fiqh Munakahat) and the traditional Uang Pelangkah tradition in Palembang, particularly in Indralaya District. Uang Pelangkah has shifted from an ethical symbol to a burdensome financial requirement that contradicts the principle of taysir (ease) in Islamic marriage, creating a burden on the prospective bride and groom. This study seeks to examine the function of Islamic Legal Education (ILE) as a driver of social transformation and to delineate the manifestations of critical acceptance within the Palembang community regarding the burdensome elements of the Uang Pelangkah tradition. The study uses a descriptive qualitative approach with field research methods. Primary data were collected through in-depth interviews and observations of young couples, traditional leaders, and ILE academics in Indralaya, Ogan Ilir. The results indicate that ILE is effective in forming critical reasoning that triggers the community to actively negotiate the tradition. This critical acceptance is manifested in the form of a drastic decrease in the nominal value, the conversion of Uang Pelangkah into a beneficial gift, or its neglect by the woman's family. As a result, ILE has succeeded in transforming mandatory customary norms into optional ethical norms that align with the maqasid al-shari'ah. This article contributes to the field of Islamic sociology of law by offering a critical reception model as an intelligent mediation mechanism between sharia and custom and affirming the ILE as a central agent in reforming social norms at the grassroots level.